2023
DOI: 10.3389/fonc.2023.1222411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of four fluoroquinolones on the viability of bladder cancer cells in 2D and 3D cultures

Abstract: IntroductionThe anticancer properties of fluoroquinolones and the high concentrations they achieve in urine may help in bladder cancer therapy. This study aimed to analyze the properties of 4 fluoroquinolones as potential candidates for supportive treatment of bladder cancer. MethodsComparative analyses were performed on the cytotoxic effects of norfloxacin, enrofloxacin, moxifloxacin, and ofloxacin on normal and cancer urothelial cell lines. In 2D culture, the cytotoxic properties of fluoroquinolones were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
1
2
1
Order By: Relevance
“…Unlike their derivatives, CIP and NOR did not induce substantial changes in spheroid growth and morphology. This last result is in contrast with the findings of other authors, who demonstrated the antiproliferative and pro-apoptotic action of CIP on human T24 bladder cancer spheroids, by observing a reduction in spheroid size and the induction of apoptosis [ 5 ]. Nevertheless, higher concentrations of fluoroquinolones were used in that work, compared to those used in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Unlike their derivatives, CIP and NOR did not induce substantial changes in spheroid growth and morphology. This last result is in contrast with the findings of other authors, who demonstrated the antiproliferative and pro-apoptotic action of CIP on human T24 bladder cancer spheroids, by observing a reduction in spheroid size and the induction of apoptosis [ 5 ]. Nevertheless, higher concentrations of fluoroquinolones were used in that work, compared to those used in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Minor to moderate toxic effects were also observed in the fibroblast cell line WH1 [ 29 ]; however, all derivatives showed higher potency on the cancer cell lines tested, compared to the fibroblast one. Interestingly, the derivatives’ better performance was also confirmed in RT112 and MCF7 spheroids, in agreement with the evidence reported by other authors, who documented the antiproliferative effects of fluoroquinolones on this 3D model [ 5 , 48 , 49 ]. These results are exciting, considering that spheroids represent an in vitro model that resembles in vivo tumor architecture and biology, mimicking the main features of solid neoplasia such as hypoxia, nutrient gradient, and cell–cell as well as cell–microenvironment interactions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations